2013
DOI: 10.21608/asnj.2013.58285
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Knowledge about Early Ambulation on Patients' Satisfaction Post Coronary Angiography , at Assiut University Hospital

Abstract: Coronary Angiography has become a main diagnostic procedure for diagnosis of Coronary Artery Disease (CAD). Aim: this study was carried out1-to investigate the impact of knowledge aboutearly ambulationon patients' satisfaction among post coronary angiography2-early ambulation after 2 hours versus 6 hours.Design: a quasiexperimental design. Setting: in catheterization and coronary care units.Subjects: A convenience sample of all adult educable and mentally competent male and female patients aged from (18-60 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Despite rapid advancement in techniques, catheters, contrast agents, and implantable devices, post-catheterization nursing care has not evolved at a similar pace, and remains classically based on bed rest, which may last 2 hours 3 to 24 hours 4 . A recent meta-analysis of 20 studies and 4,019 patients found that a bed rest duration of 2-3 hours after transfemoral catheterization is safe, has no effect on the incidence of vascular complications, and may reduce back pain and discomfort 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Despite rapid advancement in techniques, catheters, contrast agents, and implantable devices, post-catheterization nursing care has not evolved at a similar pace, and remains classically based on bed rest, which may last 2 hours 3 to 24 hours 4 . A recent meta-analysis of 20 studies and 4,019 patients found that a bed rest duration of 2-3 hours after transfemoral catheterization is safe, has no effect on the incidence of vascular complications, and may reduce back pain and discomfort 5 .…”
Section: Introductionmentioning
confidence: 99%